MySQL pocket reference - Reese, George (O'Reilly, 2007)
To help you be more efficient in your work, this handy pocket reference gives you instant reminders on how to use important MySQL functions, especially in conjunction with key parts of the LAMP open source infrastructure. This powerful database system is so rich in features that no administrator or programmer can stay familiar with all of them. MySQL Pocket Reference is an ideal on-the-job companion, well organized to help you find and adapt the statements you need -- quickly. Updated for the latest versions of this popular database, this edition covers many complex features that have been adde.